Synthesis of CuAl2O4 Nanoparticle and Its Conversion to CuO Nanorods. (7th September 2021) - Andal, V.; Buvaneswari, G.; Lakshmipathy, R.
Abstract : The molten salt approach was used to convert CuAl2 O4 nanoparticles to CuO nanorods in this study. Molten hydroxide (NaOH) synthesis was chosen over molten salts (NaCl/KCl) for removing aluminium oxide from copper aluminate at low temperatures. The molten salt process is environmentally beneficial. Polymeric precursors were used to make nanosized copper aluminates. Alginic acid polymer is used to gel aqueous solutions of copper acetate and aluminium nitrate, yielding precursor after further heating. The precursor provides 14 nm nanosized copper aluminates after being heated at 900°C for 5 hours. XRD, FTIR, SEM, and TEM were used to characterize the nanosized copper aluminate powder. Solid state mixing and solution technique were used to investigate molten hydroxide treatment of spinel CuAl2 O4 . The products of the reaction were identified using XRD. FTIR and SEM are also used to analyze the sample. Using UV-DRS absorbance spectrum analysis, the optical characteristics of CuAl2 O4 and CuO nanorods were examined. Using the Tauc plot method, the band gaps of CuAl2 O4 and CuO were calculated to be 4.3 and 3.93 eV.